Multifunctional linear‐polarized terahertz focusing metasurface. Issue 8 (5th February 2020) - Kou, Wei; Zhang, Yaxin; Chen, Ting; Yang, Ziqiang; Liang, Shixiong
Abstract: In this article, we propose a multifunctional linear‐polarized terahertz focusing metasurface enabling terahertz focusing at different focal distances for efficient terahertz wave‐front manipulation. Due to the subtle resonance response of two orthogonal electric dipoles in each unit structure, the change in length will contribute to the phase shift depending on the polarization direction of the normal terahertz wave, correspondingly, phase distributions on the metasurface can be efficiently controlled in both vertical and horizontal directions. Numerical simulations demonstrate that two different focal distances can be achieved under a normal incidence wave with different polarization. The one focal distance is 12 mm under normally incident plane wave with x polarization, while another focal distance is 4.4 mm under y ‐polarized component at 0.30 THz. This design method can significantly expand the capabilities of metasurfaces in controlling EM waves and open a pathway in designing multifunctional meta‐devices to satisfy diversified application demands.